Control continuity of commercial bank (Путеводитель предпринимателя, 2020)
Any business may be affected by a catastrophic event – fire, earthquake, terrorist attack, crashes and breakdowns of the electricity networks, etc. In this regard, the implementation of measures to ensure the continuity of the credit institution will withstand the impact of large-scale disasters on its ability to perform banking services.